(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
An analysis of literature data and the results of our own research on the characteristics of the causative agent of bovine lumpy dermatitis (LD), distribution, clinical signs, cultivation, diagnosis and prevention of the disease are presented.